Crystal structure modulating performances for 213-nm GeO2 solar-blind photodetectors via DC reactive magnetron sputtering method - Chengming Wei; Jiabao Liu; Xinru Lan; Cheng Yang; Shuiping Huang; Dongdong Meng; Zhengwei Chen; Hongguang Duan; Xu Wang (Scientific Reports)
Abstract Owing to the ultra-wide bandgap energy, high thermal conductivity, and ambipolar capability, GeO2 films are receiving great attention for potential applications in power devices and solar-blind photodetectors. However, the precise control of the crystal structure and optical property is a huge challenge due to close free formation energies of multiple phases, inhibiting the GeO2 based practical device applications. Here, we have fabricated quartz and rutile-GeO2 thin films utilizing the magnetron sputtering based synthetic strategy, which exhibit ultra-wide bandgap energies of 5.51 and 5.88 eV. On the foundation of these ultra-wide bandgap semiconductors, obvious photoresponse characteristics have been achieved at 213 nm and the quartz-GeO2 device exhibits better performances including a short fall time of 148.5 ms, a high photo-dark current ratio of 86.65, large photoresponsivity of 4.56 A/W, and high detectivity of 6.78 × 1013 Jones, which can be attributed to the less oxygen defect exists in the quartz-GeO2 film due to the oxygen-rich growth condition and the better lattice matching with sapphire. Our findings suggest that the GeO2 thin film is a candidate material for optoelectronic device applications and will provide a facile and innovative strategy to develop the solar-blind photodetector.